2021
DOI: 10.1055/a-1696-6429
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Chromium-Mediated Carbonyl Addition Reactions

Abstract: Organochromium(III) species are versatile nucleophiles in complex molecule synthesis due to their high functional group tolerance and chemoselectivity for aldehydes. Traditionally, carbonyl addition reactions of organochromium(III) species were performed through reduction of organohalides either using stoichiometric chromium(II) salts or catalytic chromium salts in the presence of stoichiometric reductants (such as manganese(0)). Recently, alternative methods emerged involving organoradical formation from read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 84 publications
(65 reference statements)
1
14
0
2
Order By: Relevance
“…Of note, 4-(methylthio)benzaldehyde was also a compatible reaction substrate, affording the corresponding product (38) with the methylthio group retained. Alcohols, as exemplified by ethanol, could also serve as suitable nucleophiles in this protocol, providing the deoxygenative 1,1-oxycarbonylation product in 53% yields (39). It is noteworthy that deoxygenative 1,1-difunctionalization of aldehydes via a tandem multicomponent reaction in one-pot is very challenging, because necleophiles can directly react with aldehydes (bimolecular reaction, for example, an acetal byproduct was detected when ethanol was used as a nucleophile) and/or deactivate metal catalysts through undesired coordination.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, 4-(methylthio)benzaldehyde was also a compatible reaction substrate, affording the corresponding product (38) with the methylthio group retained. Alcohols, as exemplified by ethanol, could also serve as suitable nucleophiles in this protocol, providing the deoxygenative 1,1-oxycarbonylation product in 53% yields (39). It is noteworthy that deoxygenative 1,1-difunctionalization of aldehydes via a tandem multicomponent reaction in one-pot is very challenging, because necleophiles can directly react with aldehydes (bimolecular reaction, for example, an acetal byproduct was detected when ethanol was used as a nucleophile) and/or deactivate metal catalysts through undesired coordination.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As a result, even though great progress has been made in C­(sp 3 )–H functionalization, including transition-metal-catalyzed C–H activation, carbene/nitrene/oxene-induced C–H insertion, and radical process triggered by hydrogen atom transfer or oxidation, a catalytic and general method for the coupling of strong alkyl C–H bonds with carbonyls remains elusive. Recently, merging chromium catalysis and photocatalysis has begun to flourish for diverse transformations, in which a carbon radical is quickly intercepted by chromium­(II) ( k = 10 7 –10 8 M –1 ·s –1 ) and further transforms into a nucleophilic organochromium­(III) species. Through activating allylic C–H bonds by oxidation/deprotonation or hydrogen-atom transfer, the Glorius and Kanai group independently developed an innovative allylation of aldehydes with alkenes by the combination of photocatalysis and chromium catalysis. , Mechanistically, the substrate scope depends on the oxidation potential of the excited *Ir III photocatalyst (∼1.21 V vs SCE) or the BDEs of thiophosphoric imide (∼87 kcal/mol, HAT catalyst).…”
Section: Introductionmentioning
confidence: 99%
“…45 A breakthrough realized in 2022 was the application of photoredox conditions to approach chromium organometallic reagents. 46…”
Section: Chromium Nucleophilic Organometallic Reagentsmentioning
confidence: 99%
“…Other reductants are either completely unreactive (Mn, Sn, In, and NiCl 2 /Mn) or undesirably reduced the aldehyde to the alcohol and pinacol byproducts (Mg, Zn, Li, Sm, SmI 2 , and Cp 2 TiCl 2 /Mn). This result is reminiscent of that of the Nozaki–Hiyama–Takai–Kishi (NHTK) reaction, in which a catalytic amount of Ni and a stoichiometric amount of CrCl 2 enable the nucleophilic addition of an organohalide to the aldehyde. After the initial hit was identified, further optimization was carried out, and it was eventually found that with CrCl 2 (2.5 equiv) and B 2 Pin 2 (1.0 equiv) as the co-reductants, 1a (0.2 mmol) reacted with 2a (0.4 mmol) to provide the desired alcohol 3a in 89% isolated yield in DMF at 90 °C after 24 h (entry 1 in Table ).…”
mentioning
confidence: 94%
“…As exemplified by the generic reaction of aldehyde 1 and pyridinium salt 2 to access alcohol 3, under thermal conditions, 2 undergoes a single-electron transfer (SET) process from coordinated Cr(II) to furnish the corresponding alkyl radical A following the release of 2,4,6triphenylpyridine. This radical intermediate is rapidly trapped by another chromium chloride through a radical-polar crossover process to afford organometallic reagent B (k = 10 7 −10 8 M −1 s −1 for chromium to trap the carbon radical), 40 which reacts with aldehyde 1 to generate alkoxide C. It is important to emphasize that the generated 2,4,6-triphenylpyridine plays a crucial role in stabilizing the alkylchromium intermediate because uncoordinated alkylchromium reagents cannot survive at 90 °C. Upon workup, the corresponding alcohol 3 is produced.…”
mentioning
confidence: 99%